2009
DOI: 10.1093/ejechocard/jep158
|View full text |Cite
|
Sign up to set email alerts
|

The role of echocardiography in guiding management in dilated cardiomyopathy

Abstract: Dilated cardiomyopathy (DCM) is a common and malignant condition, which carries a poor long-term prognosis. Underlying disease aetiologies are varied, and often carry specific implications for treatment and prognosis. The role of echocardiography is essential in not only establishing the diagnosis, but also in defining the aetiology, and understanding the pathophysiology. This article therefore explores the pivotal role of echocardiography in the evaluation and management of patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 35 publications
0
41
0
2
Order By: Relevance
“…In one study, tricuspid diastolic velocity by tissue Doppler was found to be a good prognostic measure, especially in children 13 . Other markers include LV sphericity index, diastolic filling period, presence of valvular regurgitation and presence of right ventricular changes 3 . However, these measurements need specialized machines and more importantly, trained technicians, which is not always available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study, tricuspid diastolic velocity by tissue Doppler was found to be a good prognostic measure, especially in children 13 . Other markers include LV sphericity index, diastolic filling period, presence of valvular regurgitation and presence of right ventricular changes 3 . However, these measurements need specialized machines and more importantly, trained technicians, which is not always available.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the basic pulse-Doppler echocardiography, many new techniques are now being used for better evaluation of cardiac structure and function in DCM, like tissue Doppler and speckle tracking. Echocardiography is important not only for diagnosis of the condition but also to assess prognosis and guide therapeutic interventions 3 . Besides ejection fraction, other echocardiographic measures like left and right ventricular dimensions and left atrial size and volume are also important for prognosis in these patients 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…беременности или в течение 5 мес. после родов, от имеющей худший про-гноз дилатационной кардиомиопатии (ДКМП) [1][2][3].…”
Section: Modern Methods Of Intracardiac Hemodynamics and Cardiac Defounclassified
“…Right Ventricular (RV) functions are known to have a prognostic impact on Non-Ischemic Dilated Cardiomyopathy (NICMP), similar to all forms of heart failure (1,2). RV failure due to primary Left Ventricular (LV) systolic dysfunction has been proven to be associated with worsening symptoms, hemodynamic and clinic deterioration, and increased mortality in various studies (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%